Early MRI Characteristics after MRI-Guided Laser-Assisted Cingulotomy for Intractable Pain Control - Sundararajan, S.H.; Belani, P.; Danish, S.; Keller, I. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Cingulotomy is a well-accepted stereotactic procedure in the treatment of debilitating pain syndromes. At our institution, we used a 980-nm diode laser to perform MR imaging–guided laser-assisted cingulotomy. We report the early MR imaging changes associated with this technique.MATERIALS AND METHODS: In this retrospective analysis, MR imaging–guided laser-assisted cingulotomy was performed in 4 patients with intractable pain secondary to metastatic disease. Patients were imaged at various time points postprocedure, with visual analysis of MR imaging changes in the cingulate gyri during that timeframe.RESULTS: Twenty-four hours postablation, 4 distinct zones of concentric rings reminiscent of an “owl eye” shape were noted in the cingulate gyri. Extrapolating from the imaging characteristics of the rings, we defined each zone as follows: The central zone (zone 1) represents a laser probe void with fluid, zones 2 and 3 have signal characteristics that represent hemorrhage and leaked protein, and zone 4 has a peripheral ring of acute infarction, enhancement, and surrounding edema. One patient with 1-year follow-up showed persistent concentric rings with resolution of enhancement and edema.CONCLUSIONS: Post-MR imaging–guided laser-assisted cingulotomy rings appear to represent a continuum of injury created by the laser probe and thermal injury. The imaging changes are similar to those described for laser ablation of tumor-infiltrated brain with a 1064-nm laser. This is the first study to characterize early MR imaging changes after MR imaging–guided laser-assisted cingulotomy by using a 980-nm laser. It is important for neuroradiologists and neurosurgeons to understand expected imaging findings as laser ablation cingulotomy re-emerges to treat intractable pain.MRgLACMR imaging–guided laser-assisted cingulotomy